Implementation of Banana Cultivation and Post-Harvest Technology in Wanasari Village, Purwakarta - Syariful Mubarok; Rahmat Budiarto; Fathi Rufaidah; Pipit Mutiara; Erni Suminar; Yanyan Mochamad Yani (Indonesian Journal of Community Services Cel, 2026)
Background: Bananas are among the most important horticultural commodities in Indonesia. In West Java, Purwakarta is a center of banana production. Farmers rely on traditional propagation and production methods, resulting in low yields and productivity. The main problem for banana farmers is the lack of seed availability, where almost no farmer used seed from tissue culture and only 10% of the respondent did not know about post-harvest processing technology.Aims: The aim of this activity is to improve the skills of farmers in the propagation of banana plants by in vitro culture, banana production, and post-harvest technology. This activity took place in Wanasari, Purwakarta City.Methods: The methodology for these activities was to deliver lectures and conduct practice sessions with farmers on banana propagation, production, and postharvest technology. Additionally, we provided them with a banana plant from in vitro culture.Result: The community service activity showed that the farmers were highly interested and enthusiastic about the technology introduced to them with increasing the post-test score of those audiences. The participants' enthusiasm and confidence in implementing banana cultivation and post-harvest techniques demonstrate the effectiveness and practicality of the training methods in supporting banana cultivation. This work is expected to empower farmers to manage their gardens and post-harvest banana handling, thereby contributing to economic resilience and food security.